2004
DOI: 10.1029/2003wr002759
|View full text |Cite
|
Sign up to set email alerts
|

Catchment‐scale mapping of surface grain size in gravel bed rivers using airborne digital imagery

Abstract: [1] This study develops and assesses two methods for estimating median surface grain sizes using digital image processing from centimeter-resolution airborne imagery. Digital images with ground resolutions of 3 cm and 10 cm were combined with field calibration measurements to establish predictive relationships for grain size as a function of both local image texture and local image semivariance. Independently acquired grain size data were then used to assess the algorithm performance. Results showed that for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
260
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(267 citation statements)
references
References 34 publications
6
260
1
Order By: Relevance
“…In ground-based photography (Rubin, 2004;Warrick et al, 2009) and airborne photography (Carbonneau et al, 2004(Carbonneau et al, , 2005Dugdale et al, 2010), relationships were found between grain-size properties and the pixel properties. These properties, such as pixel brightness, are measured using approaches based on spatial statistics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ground-based photography (Rubin, 2004;Warrick et al, 2009) and airborne photography (Carbonneau et al, 2004(Carbonneau et al, , 2005Dugdale et al, 2010), relationships were found between grain-size properties and the pixel properties. These properties, such as pixel brightness, are measured using approaches based on spatial statistics.…”
Section: Introductionmentioning
confidence: 99%
“…This method used as well by Warrick et al (2009) can be applied to a large range of grain sizes. The second approach based on spatial statistics consists in measuring the local semi-variance, which is a function of the difference in brightness and the distance between these pixels (Carbonneau et al, 2004). This second method was applied in airborne photography for the grain-size mapping of river catchment areas (Carbonneau et al, 2004(Carbonneau et al, , 2005Dugdale et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, image texture has been used successfully to estimate bed sediment size as areas with larger sediment have more shadows, which suggest a more heterogeneous texture (Carbonneau et al 2004(Carbonneau et al , 2005Buscombe et al 2010). Hyperspectral data have been particularly useful at this scale.…”
Section: Woody Debris (Smikrud and Prakash 2006)mentioning
confidence: 99%
“…Bed sediment size (Carbonneau et al 2004(Carbonneau et al , 2005 Bank sediment size (Rainey et al 2003) High resolution multi-spectral Hyperspectral…”
Section: Sediment Sizementioning
confidence: 99%